Chemical constituents and bioactivities of artocarpus anisophyllus MIQ - Siti Mariam Abdul Lathiff, 1989- author; Shajarahtunnur Jamil, supervisor; Fakulti Sains (2014)
Thesis (Sarjana Sains (Kimia)) - Universiti Teknologi Malaysia, 2014